Fast synthesis of optimal chemical reactor networks based on a universal system representation - Xie, Mingquan; Freund, Hannsjörg (Chemical Engineering and Processing, 2018)
We propose a new approach for the synthesis of optimal chemical reactor networks based on the concept of elementary process functions [1] and dynamic optimization. This approach is capable of incorporating process intensification options at an early design stage. Only one single differential equation is required to describe the mass balance of the whole reactor system along the reaction route. This equation contains terms describing mass fluxes from outside the reactor system and mass fluxes which flow between different positions of the reaction route. We demonstrate that different reactor types and different reactor connections can be represented by such a formulation. After solving an optimization problem using such a model, optimal profiles of state variables and fluxes are obtained. Based on these profiles, the optimal reactor system is determined. After the presentation of the theoretical background and the derivation of the new approach, it is illustrated in case studies and validated by comparison with literature results. The advantages of this new approach presented in our contribution are its simplicity in description and implementation, universality in representing different reactor types and networks, and the potential to consider different intensification and integration options at an early design stage.
Keywords: Reactor design; Process design; Optimization; Reactor network; Process intensification

Optimal reactor design and operation taking catalyst deactivation into account - Xie, Mingquan; Freund, Hannsjörg (Chemical Engineering Science, 2018)
In this work, a new approach for taking catalyst deactivation into account in the early stage of reactor design is derived and exemplified by the ethylene oxide synthesis as an industrial relevant case study. In this process, the catalyst lifetime is much larger than the residence time of reactants. The operating conditions over the whole catalyst lifetime and the reactor configuration are simultaneously optimized. The objective of the mathematical optimization problem is the overall reactor performance such as the average selectivity over the catalyst lifetime. An optimal detailed design could be derived with advanced temperature control, giving rise to a higher average selectivity and potentially longer catalyst lifetime compared to the reference case. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Reactor design; Catalyst deactivation; Optimization; Process intensification; Modeling

Process intensification by model-based design of tailor-made reactors - Freund, Hannsjörg; Maußner, Johannes; Kaiser, Markus; Xie, Mingquan (Current Opinion in Chemical Engineering, 2019)
The most recent work in the field of model-based design of catalytic reactors with a special focus on the multi-level reactor design (MLRD) methodology is reviewed. The key idea of this method is to track a fluid element on its way through the — not yet specified — reactor and to optimize the reaction conditions along its way by providing the necessary material and energy fluxes. On the basis of these optimal flux profiles novel reactor concepts tailored to the needs of the reaction system can be derived and analyzed. Recent advances and extensions to handle the specifics of reaction systems with different complexity are presented. The MLRD approach enables the predictive determination of the best reaction concept considering highly innovative process intensification options. Thereby, this method provides a key stone for the development of more economical and more sustainable chemical reactors and processes of the future.
CRIS-Team Scopus Importer:2019-10-08

Rigorous design of multiphase reactors: Identification of optimal conditions for mass transfer limited reactions - Xie, Mingquan; Freund, Hannsjörg (Chemical Engineering and Processing, 2018)
Multiphase reaction systems are often complex due to the interaction of reaction and transport processes. To design optimal reactors for such systems, a rigorous optimization is necessary. In this regard, this work proposes extensions of a reactor design methodology based on rigorous optimization. Each phase is represented by one fluid element, subject to different mass and energy fluxes. While the unlimited external fluxes are optimally provided along the reaction route, sensitivity analysis of the parameters related to the limited external fluxes is performed. The extended methodology is applied in the reactor design for chemical absorption of CO2 as an example for complex multiphase reaction systems with severe mass transfer limitation. An accurate model which is also numerically suitable for optimization has been set up and validated with pilot plant data from literature. Optimal temperature profiles which result from balancing the different temperature-dependent phenomena are identified for cases with different inlet conditions, and tailor-made heat control strategies are shown for these cases. The potential of the developments in improving mass transfer rates by, e.g., structural design or solvent design has been quantified. This model-based design methodology is generally applicable to different multiphase reaction systems with severe mass transfer limitation.
Keywords: Reactor design; Multiphase system; Mass transfer; Carbon dioxide; Chemical absorption; Process intensification